Preparation of ph-sensitive packaging film from red pitaya (Hylocereus Polyrhizus) peel for lamb meat freshness monitoring (Bangladesh Journal of Botany, 2026)
With growing demands for real-time food freshness monitoring and sustainable packaging, pH-sensitive intelligent films derived from natural pigments have gained significant attention as eco-friendly alternatives. In this study, a pH-sensitive intelligent packaging films were developed using red pitaya (Hylocereus polyrhizus) peel pigment combined with polyvinyl alcohol (PVA) and chitosan (CS). Physicochemical properties, antioxidant activity, and lamb freshness-indicating performance were evaluated. Compared to pure PVA-CS films, PVA-CS-BE films had reduced transparency, mechanical properties, and moisture content, but increased thickness and solubility. In addition, PVA-CS-BE films showed distinct pH-dependent color changes, and 3.6-fold higher DPPH scavenging. In lamb preservation, the films monitored spoilage via visible, distinguishable color changes. PVA-CS-BE films have excellent stability, antioxidant capacity, and color-indicating functionality, demonstrating significant application potential.Bangladesh J. Bot. 55(2): 395-401, 2026 (June)